Accipitridae Vigors 1824 - Somenzari, Marina; Amaral, Priscilla Prudente do; Cueto, Víctor R.; Guaraldo, André de Camargo; Jahn, Alex E.; Lima, Diego Mendes; Lima, Pedro Cerqueira; Lugarini, Camile; Machado, Caio Graco; Martinez, Jaime; Nascimento, João Luiz Xavier do; Pacheco, José Fernando; et al. (Zenodo, 2018)
Accipitridae Milvus migrans (VAG): occurs in almost the entire Old Word and Australasia, and the nominotypical subspecies is highly migratory. It breeds in continental Europe, northwestern Africa and western Asia, and overwinters mainly south of the Sahara in Africa (Ferguson-Lees & Christie, 2001). Vagrant individuals have been recorded in New Zealand and on Hawaiian islands in the Pacific. One adult individual was recently recorded in the Saint Peter and Saint Paul Archipelago, 1,100 km away from the Brazilian coast,between April 16 th and May 17 th 2014, probably by following winds from northwestern Africa (Nunes et al., 2015) that are tangent to the main flyway used by this species when moving between the wintering and breeding areas in western Europe (Sergio et al., 2014). [ Geranoaetus polyosoma ] (VAG): occurs from central Andes in Colombia to Patagonia, Tierra del Fuego, Malvinas /Falklands and Juan Fernández Islands on the coast of Chile (Bierregaard, 1994). During austral winter, birds from the Chilean Andes and from Patagonia fly north to subtropical plains in northern and eastern Argentina, Paraguay and perhaps Uruguay (Thiollay, 1994). In Brazil, there are few records: none is documented and only one has a specific locality on Cabo Frio Island in Arraial do Cabo/RJ (Pacheco, 2005). : Published as part of Somenzari, Marina, Amaral, Priscilla Prudente do, Cueto, Víctor R., Guaraldo, André de Camargo, Jahn, Alex E., Lima, Diego Mendes, Lima, Pedro Cerqueira, Lugarini, Camile, Machado, Caio Graco, Martinez, Jaime, Nascimento, João Luiz Xavier do, Pacheco, José Fernando, Paludo, Danielle, Prestes, Nêmora Pauletti, Serafini, Patrícia Pereira, Silveira, Luís Fábio, Sousa, Antônio Emanuel Barreto Alves de, Sousa, Nathália Alves de, Souza, Manuella Andrade de, Telino-Júnior, Wallace Rodrigues & Whitney, Bret Myers, 2018, An overview of migratory birds in Brazil, pp. 1-66 in Papéis Avulsos de Zoologia 58 on page 38, DOI: 10.11606/1807-0205/2018.58.03, http://zenodo.org/record/5234679 : {"references": ["Ferguson-Lees, J. & Christie, D. A. 2001. Raptors of the World. Boston, Houghton Mifflin Harcourt.", "Nunes, G. T.; Hoffmann, L. S.; Macena, B. C. L.; Bencke, G. A. & Bugoni, L. 2015. A Black Kite Milvus migrans on the Saint Peter and Saint Paul Archipelago, Brazil. Revista Brasileira de Ornitologia, 23 (1): 31 - 35.", "Sergio, F.; Tanferna, A.; De Stephanis, R.; Jimenez, L. L.; Blas, J.; Tavecchia, G.; Preatoni, D. & Hiraldo, F. 2014. Individual improvements and selective mortality shape lifelong migratory performance. Nature, 515 (7527): 410 - 413.", "Bierregaard Jr., R. O. 1994. Geranoaetus polyosoma. In: del Hoyo, J.; Elliott, A. & Sargatal, J. Handbook of the Birds of the World, Vol. 2: New World Vultures to Guineafowl. Barcelona, Lynx Edicions. 183.", "Thiollay, J. M. 1994. Family Accipitridae. In: del Hoyo, J.; Elliott, A. & Sargatal, J. (Eds.). Handbook of the Birds of the World, Vol. 2: New World Vultures to Guineafowl. Barcelona, Lynx Edicions. p. 52 - 205.", "Pacheco, J. F. 2005. Ocorrencia acidental de Buteo polyosoma (Quoy & Gaimard, 1824) na Ilha de Cabo Frio, Rio de Janeiro, Brasil. Ararajuba, 12 (2): 168 - 169."]}